INDONESIA'S STATE DEFENSE STRATEGY COUNTER-TERRORISM AS IRREGULAR WARFARE FROM A TOTAL DEFENSE SYSTEM PERSPECTIVE - Cecep Hidayat; Syaiful Anwar; T. S. L. Toruan; Luhut Simbolon (The Republic of Indonesia Defense University, 2022)
National defense is an effort to maintain territorial integrity, national safety, and state sovereignty, from disturbances and threats to the state and nation. Threats have evolved, not only military and non-military threats but also hybrids. Terrorism is a threat in the area of defense as well as security. By using qualitative research methods, this article tries to answer the question, what is the role of Indonesia in the national defense strategy to fight terrorism as an irregular war in Indonesia? From the discussion, it can be concluded that the efforts made to strengthen the national defense as a whole are to strengthen the ability to defend the state for all citizens because state defense is an integral part of the universal national defense system.